New materials in Iceland : exploring ecological and sustainable material development - Sóley Sara Eiríksdóttir 1996- (2023)
In Iceland, where most materials are imported, interest in locally-sourced alternatives is increasing. This thesis examines the landscape of sustainable material development in Iceland. The values of aesthetics and locality are explored through the scope of materials and with general research on funding opportunities and company collaborations the aim is to map the possibilities for material projects to develop their products. Five material development projects initiated by individuals from the fields of design, architecture and engineering are identified in the text. Semi-structured interviews were conducted by the author with six entrepreneurs representing five material development projects. Raw materials, funding, applications and visual representation are among the topics of the interviews. The answers show that each project has received grants from Icelandic funds, and some collaborate with companies to develop a product. Continued support from companies and funds is necessary for these materials to contribute to society. Each project is believed to be able to contribute positively towards more sustainable material usage in Iceland when the development phase reaches production by minimising waste in material processing, utilising abundant raw materials and adding to their value, and engaging in co-creation with natural resources and non-humans.